THE TEACHING PRONUNCIATION AT THE ORBIT ENGLISH COURSE PARE - Puspitasari, Ratri Eliya (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 3 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of study is to describe the teaching pronunciation at The Orbit English course Pare; the teacher preparation, the teachers’ implementation, the teachers’ evaluation and the students’ ability in pronouncing English .This research used descriptive qualitative approach as a research design. The main subject of this research was the researcher itself, the methods used in collecting data were interview, observation, and documentation. And for measure the validity of the data was using triangulation technique. The data analysis was based on three concurrent flows of activities, they were: data reduction, data display, and verification. The result of this study is show that the teachers’ preparation is bad because no syllabus and lesson plan. The teachers’ implementation that consists of: the material, media and method that teacher used in teaching pronunciation.. In pronunciation evaluation using oral test. The students’ ability in pronunciation at The Orbit English course Pare is in the good category. That is  57% in the level good.